The isl2a transcription factor regulates pituitary development in zebrafish - Yan, Chen-Yan; Wu, Feng-Yao; Sun, Feng; Fang, Ya; Zhang, Rui-Jia; Zhang, Chang-Run; Zhang, Cao-Xu; Wang, Zheng; Yang, Rui-Meng; Yang, Liu; Dong, Mei; Zhang, Qian-Yue; et al. (Frontiers in Endocrinology, 2023)
Background: ISL LIM homeobox 2, also known as insulin gene enhancer protein ISL-2 (ISL2), is a transcription factor gene that participates in a wide range of developmental events. However, the role of ISL2 in the hypothalamus-pituitary-thyroid axis is largely unknown. In the present study, we characterized the expression patterns of ISL2 and revealed its regulative role during embryogenesis using zebrafish. Methods: We used the CRISPR/Cas9 system to successfully establish homozygous ISL2-orthologue (isl2a and isl2b) knockout zebrafish. Moreover, we utilized these knockout zebrafish to analyze the pituitary and thyroid phenotypes in vivo. For further molecular characterization, in situ hybridization and immunofluorescence were performed. Results: The isl2a mutant zebrafish presented with thyroid hypoplasia, reduced whole-body levels of thyroid hormones, increased early mortality, gender imbalance, and morphological retardation during maturity. Additionally, thyrotropes, a pituitary cell type, was notably decreased during development. Importantly, the transcriptional levels of pituitary-thyroid axis hormones-encoding genes, such as tshba, cga, and tg, were significantly decreased in isl2a mutants. Finally, the thyroid dysplasia in isl2a mutant larvae may be attributed to a reduction in proliferation rather than changes in apoptosis. Conclusions: In summary, isl2a regulates the transcriptional levels of marker genes in hypothalamus-pituitary-thyroid axis, and isl2a knockout causing low thyroid hormone levels in zebrafish. Thus, isl2a identified by the present study, is a novel regulator for pituitary cell differentiation in zebrafish, resulting in thyroid gland hypoplasia and phenotypes of hypothyroidism.